PKM Usaha Dendeng Rinuak di KUB Dapur 21 Kenagarian Lubuk Basung Melalui Pelatihan Penyusunan Harga Pokok Produksi Dengan Metode Job Order Costing dan Inovasi Produk Makanan - Halmawati Halmawati; Lucy Fridayati; Al Rafni (Jurnal Eksplorasi Akuntansi, 2020)
This community service activity is motivated by the problems faced by partners, namely the rinuak business of the SME Joint Business Group Dapur 21, which is a partner group, namely economically active communities engaged in the production of traditional food based on local resources. In running their business, they are constrained by the lack of knowledge in terms of preparing the Cost of Products where many costs are needed in the production process but are not included in the calculation of product costs, especially those related to Labor Costs and Overhead Costs. Besides that, the products produced are less innovative both from the taste point of view (taste, external appearance and product processing processes which tend to be unvaried and conventional. This causes the determination of the selling price not to be in accordance with what it should be and the product quality is less developed. In addition, the impact of Covig 19 makes entrepreneurs getting worse so they need motivation so they are able to get through and survive this condition